Evaluation of the safety and efficacy of resection of endometrial polyps and submucosal fibroids in an outpatient setting in a large district general hospital in the UK - Nanak Bhagat; Sumitra Pappala; Prasanta Chattopadhyay; Sangeeta Das (Wolters Kluwer Medknow Publications, 2022)
Background: Conventionally, endometrial pathologies of varying complexity have been surgically treated as inpatients under a general or regional anesthetic. Aim: In this paper, we evaluate the safety and efficacy of hysteroscopic morcellation of endometrial pathology in the form of endometrial polyps (EPs) and submucosal fibroids in an outpatient setting for both simple and complex lesions using the Myosure™ device. Methods: Two hundred and forty-nine hysteroscopic resections were performed in an outpatient setting at the < BLINDED FOR REVIEW > from May 2014 to March 2021. The median age of the patients was 54 years. More than half of the patients presented with postmenopausal bleeding; 64% were diagnosed with EPs and 24% with submucous fibroids (SMFs). The size, topography, extension, penetration, and wall classification system scoring system were used to grade them as simple (≤4) or complex (≥5) pathologies. Results: 90% of pathologies were simple (≤4), of which complete resection was carried out in 95% of patients; 10% of the pathologies were complex (≥5), of which 63% had complete resection. Two patients with complex pathologies returned for completion surgery as a two-step procedure. No procedure was abandoned due to the patient intolerance. The median intraprocedure pain score visual analog scale was 5/10 and immediate postprocedure pain score was 1/10. Notably, there was no intra- or post-procedure complications. Conclusion: Outpatient resection of endometrial pathology, both simple and complex, can be safely and effectively performed using hysteroscopic morcellator (Myosure™) and is accepted and well tolerated by patients.